BUDAYA ORGANIZATIONAL LEARNING DAN SCHOOL BRANDING DALAM UPAYA CONTINUOUS IMPROVEMENT DI SLB DENA UPAKARA WONOSOBO - Rahmawati, Layung; Purwanto, Nurtanio Agus (Manajer Pendididikan, 2025)
Abstract - Change is an inevitability that cannot be avoided, including in the field of education. Various changes driven by technological and scientific disruptions compel special needs schools to innovate and foster a lifelong learning culture as part of continuous improvement efforts. However, there are challenges and obstacles that institutions must face in responding to the uncertainties of changing times. This article aims to examine and describe how SLB Dena Upakara responds to and addresses the challenges of change. This study employs a qualitative approach, with data collected through interviews, direct observations, and document analysis of relevant administrative records. The findings of this research are expected to provide a broader perspective on how special needs schools, as part of special education institutions, adapt to ensure a sustainable process of improving education quality. Keyword:continuous improvement, organizational learning, school branding, special school, special education